Increased Serum WISP1 Levels are Associated with Lower Extremity Atherosclerotic Disease in Patients with Type 2 Diabetes Mellitus - Cheng, Yangyang; Du, Xiaohui; Zhang, Bilin; Zhang, Junxia (Experimental and Clinical Endocrinology & Diabetes, 2021)
Background Serum wnt1-induced signaling pathway protein 1 (WISP1) levels are increased with obesity, which is a common complication associated with lower extremity atherosclerotic disease (LEAD). However, to date, the relationship between elevated WISP1 levels and the incidence of lower extremity atherosclerotic disease (LEAD) in type 2 diabetes mellitus (T2DM) remains unclear.Methods 174 newly diagnosed type 2 diabetic patients were enrolled in our study. Patients were divided into two groups, LEAD group (n=100) and control group (n=74). Anthropometric parameters, blood pressure and some biochemical parameters were obtained. Body composition was detected by bioelectrical impedance analysis (BIA). Levels of serum insulin were determined by radioimmunoassay. Serum WISP1 and interleukin 6 (IL-6) levels were determined using an enzyme-linked immunosorbent assay.Results It was shown that serum WISP1 levels in diabetic patients with LEAD were higher than those without LEAD (P<0.001). Serum WISP1 levels were positively related with waist circumference (r=0.237, P=0.003), waist-hip ratio (r=0.22, P=0.006), visceral fat area (r=0.354, P<0.001), serum creatinine (r=0.192, P=0.012), interleukin 6 (r=0.182, P=0.032), c-reactive protein (r=0.681, P<0.001), triglycerides (r=0.119, P<0.001), fasting glucose (r=0.196, P=0.011), glycated hemoglobin (r=0.284, P<0.001), and HOMA-IR (r=0.285, P<0.026). Compared with the lowest tertile, the odds ratio of the middle tertile for LEAD incidence was 3.27 (95% CI, 1.24–8.64) and 4.46 (95% CI, 1.62–12.29) for the highest tertile after adjusting confounding factors.Conclusion The results suggest that increased serum WISP1 levels independently contribute to the incidence of LEAD in patients with newly diagnosed T2DM.
Keywords: Wnt1-induced signaling pathway protein 1; lower extremity atherosclerotic disease; type 2 diabetes mellitus; obesity; inflammation; insulin resistance